Paul, the Corinthians and the Birth of Christian Hermeneutics. By Margaret M. Mitchell - Lincicum, David (The journal of theological studies, 2012)
Well known for her work on both the Corinthian correspondence and patristic Pauline interpretation, Margaret Mitchell marries these interests in this book, the published version of her 2008 Speaker's Lectures in Biblical Studies at the University of Oxford. The lively style of the original lectures—themselves a rhetorical and hermeneutical feast for those present—is here retained, with endnotes substantiating her argument with reference to the scholarly literature., Mitchell here engages in ‘reading Paul backwards and forwards’. She begins by noting how often texts from the Corinthian correspondence recur in early Christian hermeneutical reflection, and asks why ‘the road to early Christian hermeneutics run[s] through Corinth’ (p. 4).